Storytelling no podcast: as FVNexAS no gênero textual oral - Andrade, Jane Gomes de (2023)
This research presents the podcast as a non-exclusive virtual tool for learning (FVNexA) (Matos, 2020) and how its use can contribute to teaching-learning processes, especially in the production of oral textual genres, specifically storytelling. The research's general objective is to investigate how the ItemNet podcast associated with storytelling can contribute to the development of the use of orality and the production of texts in the construction of their own speeches. The methodological approach adopted was action research, as defined by Elliot (1999), Bortoni-Ricardo (2009) and Thiolente (2018). This research is structured into five chapters: In the first chapter we present a historical scenario about the orality and studies carried out it’s use. In the second chapter we discuss the theoretical foundations for carrying out this study, we provide a brief history of orality and its importance in history, we revisit the dichotomy of speech and writing, in the third we address the view on orality contained in guiding legal documents. Next, we bring the fourth chapter with the use of digital literacy and multiliteracies and the presence of technology in education. In the fifth chapter we present the methodological path of the research, we will discuss the nature of the research, the universe and participants involved, the reasons that led us to the choices discussed and the instruments selected. We develop the didactic sequence and the data obtained from the preparation of the educational podcasts. We also present the description, analysis and interpretation of this data, we reflect on the preparation of podcasts by students. Finally, we come to final considerations, references, annexes and appendices.